Superior Root Hair Formation Confers Root Efficiency in Some, But Not All, Rice Genotypes upon P Deficiency - Nestler, Josefine; Wissuwa, Matthias (Frontiers in Plant Science, 2016)
Root hairs are a low-cost way to extend root surface area, water and nutrient acquisition. This study investigated to what extend variation exists for root hair formation in rice in dependence of genotype, P supply, growth medium, and root type. In general, genotypic variation was found for three root hair properties: root hair length, density, and longevity. In low P nutrient solution more than 2-fold genotypic difference was detected for root hair length while only 1-fold variation was found in low P soil. These differences were mostly due to the ability of some genotypes to increase root hair length in response to P deficiency. In addition, we were able to show that a higher proportion of root hairs remain viable even in mature, field-grown plants under low P conditions. All investigated root hair parameters exhibited high correlations across root types which were always higher in the low P conditions compared to the high P controls. Therefore we hypothesize that a low P response leads to a systemic signal in the entire root system. The genotype DJ123 consistently had the longest root hairs under low P conditions and we estimated that, across the field-grown root system, root hairs increased the total root surface area by 31% in this genotype. This would explain why DJ123 is considered to be very root efficient in P uptake and suggests that DJ123 should be utilized as a donor in breeding for enhanced P uptake. Surprisingly, another root and P efficient genotype seemed not to rely on root hair growth upon P deficiency and therefore must contain different methods of low P adaptation. Genotypic ranking of root hair properties did change substantially with growth condition highlighting the need to phenotype plants in soil-based conditions or at least to validate results obtained in solution-based growth conditions.